Orthodontic Treatment in a Class I Bimaxillary Protrusion Malocclusion: Clinical and Cephalmomeric Results - Sharma, Jagan Nath (Orthodontic Journal of Nepal, 2011)
Esthetically pleasing face with harmonious soft tissue profile, stable occlusion and pleasant smile are important goals of orthodontic treatment. This case report along with the treatment results is of Class I bimaxillary protrusion malocclusion treated with fixed orthodontic appliance after extraction of all first premolars. The orthodontic treatment involving extraction of premolars brought about good esthetic changes in the face and dentition resulting into improvement in the soft tissue profile, occlusion and attainment of a more harmonious smile and dentofacial esthetics.